2020
DOI: 10.17993/3cemp.2020.090444.93-123
|View full text |Cite
|
Sign up to set email alerts
|

The negative effect of incivility on job satisfaction through emotional exhaustion moderated by resonant leadership

Abstract: Job dissatisfaction challenge among nurses has a remarkable impact on patient safety and quality of any healthcare system. The study examines the negative effect of workplace incivility on job satisfaction among nurses through the mediation of emotional exhaustion and helps understand the moderating role of resonant leadership between emotional exhaustion and job satisfaction. The study adopts a cross-sectional self-administered survey design to collect 129 responses of registered nurses based on a stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
3
6
0
1
Order By: Relevance
“…In particular, workplace incivility negatively influenced job satisfaction. These findings are consistent with prior results that found that uncivil behavior creates dissatisfaction among employees [ 38 , 39 ]. Our study found that workplace incivility was negatively associated with subjective well-being.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In particular, workplace incivility negatively influenced job satisfaction. These findings are consistent with prior results that found that uncivil behavior creates dissatisfaction among employees [ 38 , 39 ]. Our study found that workplace incivility was negatively associated with subjective well-being.…”
Section: Discussionsupporting
confidence: 93%
“…The association was in line with earlier investigations investigating health-related consequences across sources of incivility [ 8 , 9 , 10 , 36 , 37 ]. Our study validated the findings of prior studies [ 38 , 39 ] that indicated that workplace incivility is associated with decreased job satisfaction in the health sector. Our study findings also reveal important points for minimizing the harmful impact of workplace incivility on job satisfaction and subjective well-being.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the HRM literature, employees-related outcomes (such as satisfaction, performance, intention to stay, productivity, etc) have been extensively documented (Deni et al, 2023;Egberi & Olufolahan, 2021;Raza et al, 2023). According to Chen and Wang (2019) and Dahri et al (2020), employees' satisfaction is a pleasant emotional state generated by evaluating the employee job role. Numerous dynamics have been considered to influence the employees' satisfaction.…”
Section: Employee Satisfactionmentioning
confidence: 99%
“…Tricahyadinata, Hendryadi, Saida, and Sukisno (2020), established that incivility in the workplace has intensified due to surmounting nervousness and impractical work roles assigned to employees by supervisors or management. Extant literature (Dahri, Asif, & Mallah, 2020;Tricahyadinata et al, 2020;Vasconcelos, 2020) suggested that incivility in the workplace negatively affects the satisfaction of employees. In the human resource management (HRM) literature, the most domineering workplace incivility is related to supervisors and co workers simply due to their level of placements in the organizational hierarchy (Daniels & Jordan, 2019;Deni, Noermijati, Aisjah, & Indrawati, 2023).…”
Section: Introductionmentioning
confidence: 99%